Enhanced speed control of pipeline pigs with adjustable bypass using quantitative feedback theory and cascade PID algorithm - Xiaoxiao Zhu; Haokun Wang; Yichen Zhang; Shimin Zhang (Journal of Pipeline Science and Engineering, 2025)
During pipeline pigging operations, precise control of the pig’s running speed is crucial. However, external speed disturbances often occur during these operations. In response to this challenge, adjustments are made to the flow rate through the pig body, thereby modifying the pressure difference and achieving a targeted speed range of 1 to 3 m/s. Since a pig with an adjustable bypass port operates in a dynamically changing state, conventional control algorithms face difficulties in providing effective control. Moreover, there is limited research on speed control algorithms for pigs with adjustable bypass ports. To address these challenges, this paper introduces a control system based on quantitative feedback theory (QFT), coupled with cascaded proportional-integral-derivative (PID) tuning, for the precise speed control of a bypass pig. The state equation is derived from the pig’s operational state, and the QFT toolbox is employed to design a pre-filter and controller. This integration of QFT with cascaded PID not only facilitates both speed control and disturbance rejection but also demonstrates significantly improved control stability under variable operational conditions. The model, implemented using the Simulink toolbox, shows that this approach can quickly stabilize the pig’s speed, effectively managing continuous variations and enhancing the efficiency and safety of pipeline pigging.